Available bit rate congestion control in ATM networks developing explicit rate control algorithms. - Imer, O.C (IEEE Control systems magazine)
We present a control-theoretic approach to designing available bit rate (ABR) congestion control algorithms. ATM networks deal with different types of traffic. Among the several services offered by ATM, the ABR service plays a central role in regulating the network traffic, as it is the only service category that uses explicit feedback from the network. We present several algorithms for ABR congestion, which can adapt to the variations in the number of sources sharing a switch. These properties make this algorithm easier to apply in volatile networks, where both the network delay and the number of active sessions are not known or cannot be predicted accurately beforehand. In summary, we strongly believe that control theoretic design tools can be effectively used in designing high-performance algorithms in the context of ATM ABR congestion control